Peramalan Penjualan Produk Dengan Metode Regresi Linear Dan Aplikasi POM-QM di PT XYZ - Ilyas Aji Prakoso; Kusnadi Kusnadi; Billy Nugraha (Widya Teknik, 2021)
Forecasting is a method for estimating a value in the future or the future using past data. For forecasting in this study conducted at PT. XYZ, where this company produces fertilizers and sells it in the city and out of town, in this research the researchers discuss forecasting product sales using the exponential smoothing method and also the linear regression method and re-accurate using the POM-QM application or software. The use of these 2 forecasting methods is to obtain forecasting results that have the smallest MSE value, and in this study the data were taken from the company PT. This XYZ is data in 2019